KAJIAN PELAKSANAAN PRAKTIK PENGALAMAN LAPANGAN (PPL) MAHASISWA FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN WALISONGO SEMARANG - Achmad Hasmi Hashona (Cendekia: Kependidikan dan Kemasyarakatan, 2014)
Abstract: FieldExperience Practice (PPL) is programmed activity to student as educator candidate in school activity both in and outside class. PPL as sharpen media to studentteaching ability, in order to apply science which have been obtained bylearning in the education program. In line with target of education, Faculty Science of Tarbiyah and Teacher ship, representing one of the faculty in IAIN Walisongo Semarangenvironment, aim to develop competence and improve professionalism in the field of Islamic Education, which consist of Education Of Islamic Religion (PAI), Education Of Language Arab (PBA), Islamic Education (KI) and Tadris MIPA (Education Of Mathematics, Education Of Biology, Education Of Chemistry, Education of Physics and Education of English).This solution focused to study execution of PPL in Faculty Science of Tarbiyah and Teacher ship of IAIN Walisongo Semarang which practice at Madrasa and expected can give idea contribution and policy to improve and repair pattern of PPL with good quality and give many benefit not only for student of practical, but also for the Institute and progress of education itself. التعليم أنشطة في المحتملين كمعلمين للطلاب المبرمجة الأنشطة من سلسلة عن عبارة )PPL( هو الممارسة تجربة ىرخأ ةرابعبو ،التدريس ممارسة  في قدراتهم  لقصل  للطلاب وسيلة  PPL هو  .الدراسية  الفصول  وخارج  داخل والتعلم وتمشيا  .التعليمية  البرامج  في  إلزامية  كمادة  ممارسة  سكب الكلية  في  المحاضرات خلال  اكتسابها  تم  التي المعرفة  لتطبيق لإعداد  فدهي يذلاو ،في  Walisongo IAIN سيمارانج الكليات من واحدة  هي ،والتعليم  ةيلك ،التربية  أهداف مع  )ابب)  التعليم  ةيبرعلا الإسلامية  التربية  من  تتألف التي ،الإسلامي التعليم  مجال  في فاترحلااو  الكفاءة  زيزعتو  الخبراء والإنجليزية  ةيندبلا ةيبترلاو ،التعليم  ءايميكلا ،الأحياء  علم  والتعليم  التربية  )الرياضيات والرياضيات الإسلامية  التربية ممارسة في IAIN Walisongo تعمل  كلية والتعليم  نطاق PPL في  تنفيذ تقييم على المناقشة هذه التعليم(. وتركز ليس الفوائد  من العديد  وتوفير أنماط نوعية  ينستح لىإ ةيمارلا تاسايسلاو  الأفكار  تسهم  نأ عقوتيو  الدينية  المدارس.بالتعليم  النهوض و  للمعهد  نكلو ،طالب سراممل فقط